The Role of Lecturers and Support of Educational Personnel and Student Understanding of Program Governance the Study Will Improve the Quality of the Study Program Services - Pamungkas, R Wisnu Prio; Sinlae, Fried (Dinasti International Journal of Economics, Finance & Accounting, 2023)
The role of lecturers and support from educational staff as well as student understanding in improving study program services. The location of the activity is in the Informatics Study Program, Faculty of Computer Science, Bhayangkara University. The research method used is a quantitative method with a cause and effect relationship approach with a sample of respondents from 3 independent variables and 1 dependent variable. The sampling technique uses Proportionate Stratified Random Sampling so that it can be used proportionally according to groups or strata of the population or respondents. Analysis of the role of lecturers and support from educational staff as well as students' understanding of study program governance can improve the quality of study program services and have an impact on increasing accreditation scores. Research regarding the role of 3 (three) independent variables as discussion material is still rarely discussed in Study Program Governance. So it is necessary to consider whether students' understanding of the existence of study program services can improve the quality of study program services and will have an impact on increasing the value of study program accreditation.